2022
DOI: 10.1002/ejhf.2496
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse, death or heart transplantation in myocarditis before the introduction of immunosuppression: negative prognostic impact of female gender, fulminant onset, lower ejection fraction and serum autoantibodies

Abstract: Outcome predictors in myocarditis are not well defined; we aimed at identifying predictors of death, heart transplantation (HTx) and relapse before the introduction of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
(248 reference statements)
5
27
3
Order By: Relevance
“…Another study showed that female sex was associated with worse outcomes in patients with myocarditis. 6 In our study, the proportion of female patients was higher in FMP than in non-FMP, but sex was not associated with mortality or HTx in FMP. Histologic diagnosis is highly recommended for patients with FMP because EMB is the only method that allows the diagnosis and pathogenic clarification of myocarditis.…”
Section: Discussioncontrasting
confidence: 50%
“…Another study showed that female sex was associated with worse outcomes in patients with myocarditis. 6 In our study, the proportion of female patients was higher in FMP than in non-FMP, but sex was not associated with mortality or HTx in FMP. Histologic diagnosis is highly recommended for patients with FMP because EMB is the only method that allows the diagnosis and pathogenic clarification of myocarditis.…”
Section: Discussioncontrasting
confidence: 50%
“…Survival free from death or heart transplantation at 10 years was 83% and was lower in biopsy‐proven versus clinically suspected myocarditis (76% vs. 94%, p < 0.001). Female gender, fulminant presentation, anti‐nuclear antibodies and lower LVEF were predictors of death or heart transplantation 24 …”
Section: Discussionmentioning
confidence: 99%
“…Female gender, fulminant presentation, anti-nuclear antibodies and lower LVEF were predictors of death or heart transplantation. 24…”
mentioning
confidence: 99%
“…Clinical myocarditis phenotypes have established prognostic value. For example, hemodynamic compromise with cardiogenic shock, the presence of ventricular arrhythmias, high-grade heart block, female sex and lower left and right ventricular systolic function increase the risk of subsequent death or heart transplantation [ 97 , 98 ]. However, the features on heart biopsy histology and cardiovascular magnetic resonance imaging (MRI) that guide therapy are limited to a few uncommon conditions, such as giant cell or eosinophilic myocarditis.…”
Section: Clinical Presentationmentioning
confidence: 99%